Fektivitas Penjualan Online dan Offline terhadap Kepuasan Konsumen di Wilayah Kota Kupang - Ruperta Intan Natu; Queen Amelia Safitri; Fella Anggrayni Akulain; Yohanis Pemandi Lian (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
The shift toward digital shopping has changed how consumers evaluate convenience, product certainty, and transactional security. In Kupang City, both online and offline channels continue to be used, yet consumers often experience different levels of trust and satisfaction across these platforms. This study aims to examine how trust, shopping experience, and consumer perceptions shape satisfaction in both online and offline purchases. A descriptive qualitative approach was employed, using a mixed-format questionnaire distributed to consumers who had purchased through both channels. Responses were analyzed by grouping similar statements to identify recurring patterns related to convenience, product assurance, and service quality. The findings show that online shopping is valued for its practicality, efficient access, and wider product options, although issues such as product mismatch and delivery delays remain common. Offline shopping is perceived as more reliable due to direct product inspection and face-to-face interaction, which strengthen trust and reduce perceived risk. Overall, the study indicates that each channel contributes differently to consumer satisfaction: online purchases emphasize convenience, while offline purchases highlight security and quality certainty. These results suggest that businesses can benefit from integrating both channels to address diverse consumer needs in Kupang City.